A Description Of Motivation Ners Professional Program In The Clinical Learning Process - Dewi Suryaningsi Hiola (Cita konsultindo, 2024)
The nursing professional program is a continuation program from the undergraduate nursing program to become a nurse. In the nursing professional stage, students are directly involved in clinical service settings, therefore students will directly interact with patients, clinical supervisors, and the clinical environment. During the professional program, students are not easy. Various problems and obstacles faced may never have been imagined before. Therefore, the motivation of each prospective nurse needs to be monitored at various stages of the professional program. Learning motivation is a drive in students, both intrinsic and extrinsic, which can lead to more effective learning activities. This study is a quantitative research type using descriptive analysis with a survey approach. The study population was 135 students with a sample of 122 who were willing to become respondents and fill out the questionnaire using a total sampling technique. Data analysis used univariate tests. The results showed that students with learning motivation were categorized as high with a total of 94 respondents (77.0%), 27 respondents (22.1%) were in the moderate category, and 1 respondent (0.8%) was in the low category. This research is expected to provide input for policy makers at the Nursing Study Program at Gorontalo State University to better maintain the motivation of Nursing professional students in the learning process.